Effects on Oxidative Stress and Antioxidant Enzyme Activities of Experimentally Induced Ornithobacterium rhinotracheale Infection in Broilers - Benzer, Fulya; Yilmaz, Seval (Medwell Online, 2009)
This experiment was conducted to evaluate the effects of Ornithobacterium rhinotracheale (ORT) infection on oxidative stress and the activity of antioxidant enzymes in blood, trachea and lung tissues of broilers. Broiler chickens were divided into 2 groups, each consisting of 30 animals. Group 1 was used as control group; Group 2 was used as infection group. The 2nd group was infected by aerosol route with 1 mL of a pure culture of ORT strain B3263/91 (serotype A) containing 3.8x10(8) CFU mL(-1). At the end of the experiment blood and tissue samples were collected and biochemical parameters were determined. While, plasma Malondialdehyde (MDA) and Nitric Oxide (NO) levels were increasing at infection group than control group, erythrocyte Catalase (CAT) and Glutathione Peroxidase (GSH-Px) activities were decreasing in accordance with control group. Levels of MDA and NO in trachea tissue increased at infection group more than control group; but activities of CAT and GSH-Px did not change. MDA level and CAT activity increased in lung tissue, however level of NO decreased more than the control group. GSH-Px activity had no change statistically. There are alterations in wide array of oxidants and antioxidants, with balance shifting toward increased oxidative stress in ORT infection. Therapeutic augmentation of the antioxidant defenses might be beneficial.
Keywords: Ornithobacterium rhinotracheale; broilers; lipid peroxidation; antioxidant; nitric oxide